2021
DOI: 10.3389/fpubh.2021.769238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Environmental and Occupational Risk Factors for the Mitigation and Containment of a COVID-19 Outbreak in a Meat Processing Plant

Abstract: Throughout the COVID-19 pandemic, meat processing plants have been vulnerable to outbreaks of SARS-CoV-2 infection. Transmission of the virus is difficult to control in these settings because of a combination of factors including environmental conditions and the specific nature of the work. This paper describes a retrospective outbreak investigation in a meat processing plant, a description of the measures taken to prevent or contain further outbreaks, and insights on how those with specific knowledge of the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…The exhaled fine droplets and aerosol particles from infected persons can build up in a confined space, attach to surfaces, and would be transferred through airflow or contact [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhaled fine droplets and aerosol particles from infected persons can build up in a confined space, attach to surfaces, and would be transferred through airflow or contact [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most environmental infection-related incidents occur in crowded cities in economically developed cities. However, it remains unclear about SARS-CoV-2 spill-over effect of environmental fomites, and the role of the environment could play in pathogenesis, spread, and severity of COVID-19 [ 30 ]. In addition, the COVID-19 has brought both positive and negative environmental impacts, especially warning and response from nature would alert humans and provide insights for contamination on further aggravation of the pandemic [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cumulative incidence estimates of SARS-CoV-2 infection have varied across job roles in both the agricultural and food production sectors [ 2 , 9 ]. Drivers of workplace transmission are similar among these sectors and include the inability to physically distance, physically demanding work, poorly ventilated indoor spaces, insufficient or inadequate personal protective equipment, congregate living and transportation, and incentivized productivity standards that may encourage working while experiencing symptoms [ 31 , 32 , 33 , 34 ]. Transmission dynamics were not assessed in this analysis, but the association between seropositivity at enrollment and job roles suggests that workplace transmission may have contributed to the high seroprevalence estimates in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Given that increased risk for SARS-CoV-2 infection is associated with occupational setting and job role, workplace prevention strategies are imperative to decrease COVID-19 incidence within the agricultural sector. Several workplace prevention measures implemented in agricultural and food processing settings have been suggested to mitigate worker risk for SARS-CoV-2 infection [ 1 , 32 , 33 , 34 ] and include onsite-testing and vaccination, use of plexiglass dividers, restricted building access for non-employees, increased frequency of worksite shuttles to minimize crowding, daily symptom checks and questionnaires, posted health education materials, close coordination with local public health authorities, and employer-provided personal protective equipment. In July 2020, the agribusiness instituted a systematic workplace prevention plan in accordance with guidelines set forth by the Ministerio de Salud y Asistencia Social [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that rather than particular areas of the hospital being associated with higher risk of infection, it is the activity of the individual which is the most important risk factor; workers dealing directly with SARS-CoV-2 positive patients, regardless of role, are at increased risk of infection. Ventilation and PPE use as well as the general prevalence of infection in the population are also factors that influence risk of infection both in hospitals and other locations [64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%